Vulnerability to xylem embolism as a major correlate of the environmental distribution of rain forest species on a tropical island. (16th December 2016) - Trueba, Santiago; Pouteau, Robin; Lens, Frederic; Feild, Taylor S.; Isnard, Sandrine; Olson, Mark E.; Delzon, Sylvain
Abstract: Increases in drought‐induced tree mortality are being observed in tropical rain forests worldwide and are also likely to affect the geographical distribution of tropical vegetation. However, the mechanisms underlying the drought vulnerability and environmental distribution of tropical species have been little studied. We measured vulnerability to xylem embolism ( P 50 ) of 13 woody species endemic to New Caledonia and with different xylem conduit morphologies. We examined the relation between P 50, along with other leaf and xylem functional traits, and a range of habitat variables. Selected species had P 50 values ranging between −4.03 and −2.00 MPa with most species falling in a narrow range of resistance to embolism above −2.7 MPa. Embolism vulnerability was significantly correlated with elevation, mean annual temperature and percentage of species occurrences located in rain forest habitats. Xylem conduit type did not explain variation in P 50 . Commonly used functional traits such as wood density and leaf traits were not related to embolism vulnerability. Xylem embolism vulnerability stands out among other commonly used functional traits as a major driver of species environmental distribution. Drought‐induced xylem embolism vulnerability behaves as a physiological trait closely associated with the habitat occupation of rain forest woody species. Abstract : Increases in drought‐induced tree mortality are being observed in tropical rain forests worldwide and are also likely to affect the geographical distribution of tropical vegetation. However, the mechanisms underlying the drought vulnerability and environmental distribution of tropical species have been little studied. Trueba et al . measured vulnerability to xylem embolism, along with other easy‐to‐measure wood and leaf functional traits, of 13 species endemic to the tropical archipelago of New Caledonia. This study shows that xylem embolism vulnerability stands out among other functional traits as a major driver of species environmental distribution. Drought‐induced xylem embolism vulnerability behaves as a physiological trait closely associated with the habitat occupation of rain forest woody species.